LEGAL PROTECTION OF THE SALE AND PURCHASE OF LAND RIGHTS THAT HAVE NOT BEEN REGISTERED - Lisa Komala Dewi; Tjempaka (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This article aims to discuss the legal consequences of buying and selling land rights that have not been registered and legal protection for buying and selling land rights that have not been registered. This article uses normative legal research methods. The nature of the research is descriptive analysis. The primary legal materials used in this writing are the 1945 Constitution of the Republic of Indonesia, Law Number 5 of 1960 concerning Basic Agrarian Regulations, Government Regulation Number 24 of 1997 concerning Land Registration, and Government Regulation of the Republic of Indonesia Number 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration. As for secondary legal materials in the form of publications on law including text books, legal dictionaries, legal journals, and comments on court decisions. The tertiary legal materials used in this research are the Big Indonesian Dictionary and the Legal Dictionary. The results of the research show that the legal consequences of transferring rights due to the sale and purchase of land that has not been registered are legally valid if the transfer of land rights is due to the sale and purchase of land that has not been registered. the registration has met the material requirements for sale and purchase, namely "bright" and "Cash". Legal protection for buyers of land rights due to the sale and purchase of land that has not been registered will still receive legal protection if those who obtain it are in good faith, namely in the form of repressive legal protection, namely legal protection which is directed more towards efforts to resolve disputes, as an example is the settlement of disputes in court,